Effect of age and contact lens wear on corneal epithelial dendritic cell distribution, density, and morphology. Issue 1 (February 2020) - Golebiowski, Blanka; Chao, Cecilia; Bui, Kim Anh; Lam, Wing Yan Winnie; Richdale, Kathryn; Stapleton, Fiona
Highlights: Density, distribution and morphology of corneal epithelial dendritic cells (CEDC) do not differ in established contact lens wearers. Reduced CEDC density in the corneal centre observed in orthokeratology lens wear requires confirmation in a larger group. CEDC in the central cornea were similar in density and morphology to CEDC cells in the mid-peripheral cornea. A lower ratio of central relative to mid-peripheral density of CEDC occurs with younger age. A relatively lower density of CEDC in the corneal centre vs mid-periphery in younger patients may reflect a more naive immune status. Abstract: Purpose: Contact lens wearers aged 15–25 years are at higher risk of corneal inflammation, yet little is known about corneal inflammatory state in this group. Previous investigations show density of corneal epithelial dendritic cells (CEDC) may increase with contact lens wear. However, it is not known how corneal distribution or morphology of CEDC alters with lens wear or whether these markers are affected by age. This study characterised CEDC in adolescent and young adult contact lens wearers to determine effects of contact lens wear and age on CEDC density, distribution and morphology. Method: Forty participants (20 contact lens wearers, 20 healthy non-wearers; age 16–36 years; 16M:24F) completed this pilot study. Corneal images were captured using in vivo confocal microscopy (HRTII, Rostock). CEDC were manually counted in a 1 mm 2 area of the central and mid-peripheral cornea, and ratio of central to midperipheral density was calculated. CEDC morphology and dendrite length were graded. Differences between groups and between regions, and associations with age were examined. Significance was determined at P < 0.05. Results: A lower ratio of central to mid-peripheral CEDC density was found with younger age (ρ = 0.42, P = 0.01). CEDC morphology was not associated with age or contact lens wear. CEDC density in the mid-peripheral cornea was higher in soft lens wearers than non-wearers (P = 0.04), but central density did not differ. CEDC density and morphology were not significantly different between centre (median density 11 cells/mm 2, range 0–120) and mid-periphery (10 cells/mm 2, 0–58). Conclusion: Density, distribution and morphology of CEDC do not differ in established contact lens wearers. A relatively lower density of CEDC in the central cornea of younger patients may allude to a more naive immune status in this group and warrants further study. Decreased central CEDC density identified in orthokeratology lens wear requires confirmation in a larger group.